Estrategia metodológica y su aporte en el aprendizaje significativo de los estudiantes de quinto semestre de la Carrera PCEI del periodo abril-septiembre 2022 - Yépez Delgado, Ederita Jazmín (2022)
The present titling work was carried out to solve a conceptual problem related to methodological strategies and meaningful learning, for this reason, following a conviction, the objective of listing the contributions of methodological strategies in meaningful learning was raised, being the work designed and investigated in the PCEI career for which the collaboration of 68 students of the previously described career was requested, for which a descriptive profile was followed that allows deductively relating the contributions that these strategies have come to have in improving the quality of thought of the students who study said career, for which a questionnaire comprised of 10 questions was elaborated using the Likert scale, and concluded that the methodological strategies applied do not cover the entire classroom where there are dissatisfied students, that although it is true it is the minority, but it is an issue that must be addressed to reduce Circumcise this figure, for which it is recommended that methodological strategies be used properly, in this way the correct use will allow students to become familiar with each of the characteristics they possess, also allowing students to know more about knowing them and knowing how to recognize them when they are applied in other educational institutions.